Peran Electronic Word Of Mouth Terhadap Keputusan Pembelian Ulang: Citra Merek Sebagai Mediasi - Delviana, Ajeng Sukma; Sarwoko, Endi; Hidayat, Candra Wahyu (MBR (Management and Business Review), 2023)
The research aims to investigate the role of electronic word of mouth (e-WOM) on repurchase decisions, in addition to revealing the mediating role of brand image. Using a quantitative research approach, the survey research type of 108 respondents using Marcks powder products in Malang City, was determined using a purposive sampling technique. Data was collected using a questionnaire distributed online, then hypothesis testing used the Path Analysis method. The results of this research reveal that e-wom has a positive influence on brand image and repurchase decisions, in addition, it was found that the indirect influence of e-wom on repurchase decisions is mediated by brand image. Product promotion using e-WOM contributes to improving brand image which can then encourage repurchase decisions